2021
DOI: 10.3390/ijerph18062882
|View full text |Cite
|
Sign up to set email alerts
|

Is Mindfulness-Based Stress Reduction Effective for People with Hypertension? A Systematic Review and Meta-Analysis of 30 Years of Evidence

Abstract: Background: Hypertension is among the most important risk factors for cardiovascular diseases, which are considered high mortality risk medical conditions. To date, several studies have reported positive effects of mindfulness-based stress reduction (MBSR) interventions on physical and psychological well-being in other medical conditions, but no meta-analysis on MBSR programs for hypertension has been conducted. Objectives: The objective of this study was to determine the effectiveness of MBSR programs for hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 76 publications
(157 reference statements)
2
32
0
13
Order By: Relevance
“…Several different definitions of mindfulness share one common element: the non-judgemental attitude toward one's inner experience (21,22). Recent evidence showed the potentially protective role of mindfulness skills against the development and maintenance of psychological distress during the pandemic, but not only, in various populations [e.g., (23)(24)(25)]. Previous evidence suggested that CHS people show lower mindfulness skills, as compared with those not reporting such symptoms (26).…”
Section: Introductionmentioning
confidence: 99%
“…Several different definitions of mindfulness share one common element: the non-judgemental attitude toward one's inner experience (21,22). Recent evidence showed the potentially protective role of mindfulness skills against the development and maintenance of psychological distress during the pandemic, but not only, in various populations [e.g., (23)(24)(25)]. Previous evidence suggested that CHS people show lower mindfulness skills, as compared with those not reporting such symptoms (26).…”
Section: Introductionmentioning
confidence: 99%
“…It highlights on practicing intentionally focusing towards the consciousness on one's experiences about the present instance without judgment. e main focus of this program is to concentrate towards enthusiasm, acceptance, and openness towards the present moment which is supported by a set of formal and informal practices where the former consists of body scan meditation and walking meditation and the latter follows emotional connections, interpersonal communications, awareness, and experience towards daily events [9]. e regular practice of MBSR is considered to diminish BP in multiple ways including reduction of psychological stress and mood switching that are linked with hypertension and CVD [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“… 55 There is also an indication of improved myocardial and endothelial function from meditation practice in patients with microvascular angina, 56 and reduction in markers of inflammation. 57 58 MBIs have been shown to reduce hypertension in a recent meta-analysis, 59 contribute to weight loss and blood-sugar levels 60 61 and reduce smoking. 62 …”
Section: Discussionmentioning
confidence: 99%